POTENTIAL OF ROSELLA HIBISCUS SABDARIFFA L) AS A HERBAL MEDICINE FOR HEALTH - Bakara, Sri Muliana Putri; Sinaga, Siti Nurmawan; Manurung, Herna Rinayanti; Damanik, Oktavania; Bakara, Cristoboy Vasius; Gulo, Paslina (Journal of Public Health Science, 2024)
Hibiscus Sabdariffa L usually called the rosella plant, is a plant that has many benefits starting from the petals, leaves, seeds, and stems, has been used as an herbal medicinal plant since ancient times with a variety of substances that are good for the human body. Hibiscus Sabdariffa L contains antioxidants, anti-diabetes, as a diuretic, anti-cholesterol, anti-cancer, anti-microbial, anti-inflammatory, anti-lipidemic, anti-hypertensive, and immunomodulatory agent. This literature summarises some of the nutritional benefits of rosella and its potential use as a herbal medicine. This literature method uses a systematic review. The database used is PUBMED, Science Direct, and Google Scholar. Using keywords that correspond to the potential of the Hibiscus Sabdariffa plant for health, 15 articles were obtained in Indonesian and English. There have been various studies related to the nutritional content of the Hibiscus Sabdariffa L plant which has great potential to be used as an herbal medicinal ingredient that has many benefits and is safe for consumption every day which is discussed in this review.